Pola Asuh Kiai Imam Yahya Mahrus: Studi Kasus di Pondok Pesantren HM Al-Mahrusiyah Lirboyo Kediri - Putri Lailatul Komariyah (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study examines parenting patterns in Islamic boarding schools (pesantren). While the parenting model generally practiced by Kiai and Bu Nyai is considered paternalistic, this research explores the possibility of another or derivative parenting model. The study was conducted at HM Al-Mahrusiyah Islamic Boarding School, Lirboyo, Kediri City, founded by the late Kiai Imam Yahya Mahrus and currently home to approximately 10,000 students from diverse ethnic and cultural backgrounds across Indonesia. Despite this diversity, the parenting pattern established by Kiai Imam Yahya Mahrus and continued by his successors has successfully supported the institution's rapid development. Guided by the qualitative tradition of Max Weber's Verstehen theory, this study finds that Kiai Imam Yahya Mahrus tended to apply a democratic parenting pattern based on the principle that every student was regarded as his own child, expressed in the Javanese phrase Santriku yo Anakku (